(untitled) (Comprehensive Journal of Science, 2025)
This research aims to examine the role of modern technology in transforming modern economies by analyzing its impact on digital infrastructure, human capital, innovation, economic performance, and sustainability. The study adopted a descriptive-analytical methodology supported by a field survey of 30 participants from various institutions. The results indicate that institutions with advanced digital infrastructure achieve higher productivity, lower operational costs, and improved competitiveness. However, the study also reveals persistent challenges, such as the digital skills gap and limited technological innovation, which hinder effective transformation. The study recommends adopting national digital transformation strategies, increasing investment in human capital development, and supporting research and technological innovation to achieve sustainable economic growth.